EDUCATION OF YOUNG PEOPLE AND ADULTS: REFLECTIONS FROM A DIALOGICAL APPROACH - Neves França, Atila (Revista Gênero e Interdisciplinaridade, 2025)
This article presents a critical and experiential reflection on the pedagogical practice in Youth and Adult Education (EJA), based on the experiences of a teacher from the public school system in the state of Mato Grosso, who worked in night-time EJA with multi-grade classes composed mainly of adults and elderly people. It starts from the observation that, more than curricular content, students in this modality need emotional support, recognition of their life stories and pedagogical proposals that respect their rhythms and singularities. The lack of specific teaching materials for EJA for teachers suggests the need to create their own resources, often without adequate training for this. In addition, there is a lack of a unified diagnostic assessment for the modality, which makes it difficult to identify learning indicators and limits the construction of more effective public policies. Based on the principles of andragogy and educational psychology, the author proposes practices such as autobiographical writing, active listening and cultural scripts as strategies for belonging and motivation. The urgent need to implement an “EJA Pact” is also highlighted, with a database of questions, external application of assessments and standardized pedagogical reports for the public school system. The article argues that EJA should be recognized as a space for a new beginning, empowerment and social appreciation of historically excluded individuals, and that it should be consolidated with permanent teacher training policies, production of structured material and intersectoral actions. The experience reported reveals that, when the student feels welcomed and valued, there is an increase in attendance, engagement and self-esteem, transforming the school into a space for belonging and reconstruction of meaning.